2023
DOI: 10.1021/acs.jpcc.2c08222
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Degradation of Na2Ni[Fe(CN)6] Functional Electrodes in Aqueous Media: A Combined Theoretical and Experimental Study

Abstract: Prussian blue analogues (PBAs) are versatile functional materials with numerous applications ranging from electrocatalysis and batteries to sensors and electrochromic devices. Their electrochemical performance involving long-term cycling stability strongly depends on the electrolyte composition. In this work, we use density functional theory calculations and experiments to elucidate the mechanisms of degradation of model Na2Ni­[Fe­(CN)6] functional electrodes in aqueous electrolytes. Next to the solution pH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…To account for the two stages of the mechanism, an adsorption capacitance C a,2 and resistance R a,2 are added to the Randles circuit. 34 Hereby, the model reflects the fact that the reduction of the first carbonyl group determines the second step of the redox process, which unquestionably takes place after the transfer of the first electron. Thus, the two stages are conjugated, and C a,2 , and R a,2 are connected in the circuit accordingly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To account for the two stages of the mechanism, an adsorption capacitance C a,2 and resistance R a,2 are added to the Randles circuit. 34 Hereby, the model reflects the fact that the reduction of the first carbonyl group determines the second step of the redox process, which unquestionably takes place after the transfer of the first electron. Thus, the two stages are conjugated, and C a,2 , and R a,2 are connected in the circuit accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously to the primary two-stage conjugated mechanism, a one-electron single-stage mechanism was found to take place. This process can be modeled by a charge transfer resistance R ct,1 and an adsorption capacitance C a,1 34 that are connected in parallel to the elements representing the two-stage mechanism. By including these parameters, the spectra can be fitted with extremely high accuracy for all potentials, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 are discussed in section S2 of the supplementary text. [36][37][38] Collectively, the potential drift profiles from Figs. 3b and 4 indicated that there were no significant contributions from electrode dissolution, faradaic processes, or other experimental anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…As exemplarily shown in Figure S1, stable performance of the thin-film electrodes is obtained at low and high C-rates along with a coulombic efficiency close to 100%. A more detailed analysis and discussion of the stability of PBAs in aqueous electrolytes is available in our previous work. , Since the composite electrode had a much higher absolute capacity compared to the thin-film electrodes, a symmetric WE-CE configuration was set up using a largely oversized CE, which was previously brought to 50% state-of-charge. The measurement protocols involved CV scans at different rates and galvanostatic cycling with potential limitations at varying C-rates.…”
Section: Methodsmentioning
confidence: 99%